(untitled) (Research, Society and Development, 2021)
Information and communication technologies – ICT are inserted in the daily life of the population, interfering in social, professional and educational relationships. Among the interactive resources provided by ICT are learning objects, including simulations. Thus, this article presents partial results of a doctoral research, and aims to investigate the contributions, potentials and difficulties of using simulations for the teaching and learning process of Genetics, according to the 4th year students of the Integrated Administration in a public school in the city of Paranavaí. The methodology adopted is of a qualitative nature, of the participant observation type, in which a didactic sequence was implemented, using the resources of Google Classroom, associated with the use of simulations. Subsequently, a post-test questionnaire was applied, the results of which are presented in this article. Among the main advantages of the environment listed by the students are: they facilitate the learning of genetic concepts and allow for methodological diversification. And as positive aspects: facilitate learning, organization and practicality of resources; make the class more dynamic; the illustration and the ease of access. And as negative aspects: difficulty and complexity in carrying out activities; internet access; and the low quality of appearance of the simulations. It was concluded that the use of simulations can be an excellent tool for didactic-pedagogical purposes, if used in a planned way, as it can facilitate learning, enable a methodological diversification; assist in the organization of content and in the interaction between participants.